1994
DOI: 10.1007/bf00048311
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin production in cultured cells of Aralia cordata Thunb.

Abstract: High anthocyanin-producing cell lines, which were grown in a dark or in a light-dark regime, were selected from callus cultures initiated from stem and leaf tissues of Aralia cordata Thunb. by small-cell-aggregate selection. To verify the optimum culture conditions for anthocyanin production, cells were tested by changing the various basal media, sucrose concentration and nitrogen source and concentration. Good growth was obtained in the dark on Linsmaier-Skoog's basal medium containing 1.0 mg 1-1 2,4-D and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 21 publications
3
24
0
1
Order By: Relevance
“…This feature will certainly offer us a way to control the production of secondary metabolites in cultures. Many reports have confirmed that callus and root growth, as well as secondary metabolite accumulation are promoted under the influence of NO 3 -in cell cultures of W. somnifera and Aralia cordata (Sakamoto et al 1994). …”
Section: Resultsmentioning
confidence: 90%
“…This feature will certainly offer us a way to control the production of secondary metabolites in cultures. Many reports have confirmed that callus and root growth, as well as secondary metabolite accumulation are promoted under the influence of NO 3 -in cell cultures of W. somnifera and Aralia cordata (Sakamoto et al 1994). …”
Section: Resultsmentioning
confidence: 90%
“…It was hypothesized that the ratio of NH 4 ? to NO 3 -nitrogen improved anthocyanin production, which was mainly due to change in primary cellular metabolism (Yamakawa et al 1983;Sakamoto et al 1994;Sato et al 1996;KonczakIslam et al 2001;Nagira and Ozeki 2004).…”
Section: Effects Of Nhmentioning
confidence: 97%
“…ratio in the medium was found to decrease the cellular syntheses of berberine in Thalictrum minus and ubiquinone in Nicotiana tabacum (Nakagawa et al 1984;Ikeda et al 1977) and of alkaloids in Atropa belladonna hairy roots (Bensaddek et al 2001). The total nitrogen content is also a contributing factor (Sakamoto et al 1994). The ammonium/nitrate ratio controls the pH of the growth media, stimulates morphogenesis and embryogenesis, and thus is important for inducing callus formation in many woody plant cultures.…”
mentioning
confidence: 99%